Comments of the AFAANZ Auditing and Assurance Standards Committee on Proposed International Standard on Auditing 600 (ED 600). (6th April 2021) - Coram, Paul J.; Harding, Noel; Hay, David C.; Khan, Jahanzeb; Prasad, Ashna
Abstract: The International Auditing and Assurance Standards Board (IAASB) issued for public comment Proposed International Standard on Auditing 600 (Revised) 'Special Considerations – Audits of Group Financial Statements (Including the Work of Component Auditors) (ED 600). The Australian Auditing and Assurance Standards Board (AUASB) and New Zealand Auditing and Assurance Standards Board (NZAuASB) also called for comments. The Auditing and Assurance Standards Committee of AFAANZ prepared a submission, based on the findings reported in extant research, responding to a number of the questions asked by the IAASB (and AUASB/NZAuASB). This commentary presents the formal submission made to the IAASB (and AUASB/NZAuASB).